2014
DOI: 10.5115/acb.2014.47.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Harris lines observed in human skeletons of Joseon Dynasty, Korea

Abstract: The Harris line (HL), caused by bone-growth arrest and manifesting on X-rays as a radiopaque transverse line in the metaphysis of the long bones, is an indicator reflecting stress conditions such as disease or malnutrition. HL frequency has been assumed to differ between pre-modern and modern societies, as reflective of increased caloric intake and overall nutritional improvements attendant on industrialization. To determine if such a change occurred in Korea, in the present study we compared the respective HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Similarly, within the adult sample, more HLs were recorded on the younger individuals, although the statistical difference was not significant. The same trend was previously observed in two attritional cemeteries (Gilde, ; Beom et al, ). This decrease of HL prevalence is consistent with a more prolonged remodeling process on older individuals due to their age‐at‐death.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, within the adult sample, more HLs were recorded on the younger individuals, although the statistical difference was not significant. The same trend was previously observed in two attritional cemeteries (Gilde, ; Beom et al, ). This decrease of HL prevalence is consistent with a more prolonged remodeling process on older individuals due to their age‐at‐death.…”
Section: Discussionsupporting
confidence: 88%
“…Over the past several years, we have endeavored to build a human sample collection consisting of skeletons discovered in 16th-18th century Joseon cemeteries in Korea. In fact, our previous studies have yielded clarifying data on the health and disease statuses of pre-modern Joseon peoples [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. In the present study, to contribute to a better understanding of the food-intake patterns of pre-modern Joseon populations in Korean history, we tried to perform a stable isotope analysis on skeletons from the same Joseon collection.…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of chondrocytes proliferation or differentiation (presented on the right side) makes the growth plate impenetrable for osteoblasts, which in turn begin to create a mineralized layer along the horizontal layer of chondrocytes at the end of the epiphyseal plate; they form a primary stratum perpendicular to the long axis of the medullary cavity. Prolonged periods of growth arrest result in the thickening of the primary stratum, which leads to the deposition of a Harris line (Scott and Hoppa 2015) populations found in numerous studies (Piontek et al 2001;Beom et al 2014;Geber 2014;Zapala et al 2016;Krenz-Niedbała 2017). In addition, even if it will be concluded that HLs are poorly suited for determining the health of individuals (as it may be a result of non-pathological processes), they can still be useful for determining the overall health at the population level (Nowak and Piontek 2002b): assuming that the occurrence of HL unassociated with any pathologies is (more or less) constant, statistically different frequency of HL between the compared populations would result from different occurrence of HL associated with pathologies or physiological stress.…”
Section: Introductionmentioning
confidence: 96%
“…There was no statistically significant correlation between bone length and morphology and the occurrence of HL (Mays 1985;Nowak and Piontek 2002b). Moreover, numerous researchers have failed to find correlations between the age of enamel hypoplasia (EH) and HL formation, suggesting that HLs are a physiological rather than a pathological phenomenon (Piontek et al 2001;Beom et al 2014;Geber 2014;Zapala et al 2016;Krenz-Niedbała 2017). Due to the similarities between the somatotropin (growth hormone) secretion curves, the long bone growth curves, and the distribution of HLs, it was suggested that HLs are associated with physiological periods of faster and slower growth (Papageorgopoulou et al 2011).…”
Section: Introductionmentioning
confidence: 99%